2017
DOI: 10.1051/epjconf/201716501002
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured surfaces for nuclear astrophysics studies in laser-plasmas

Abstract: Abstract. The future availability of high-intensity laser facilities capable of delivering tens of petawatts of power (e.g. ELI-NP) into small volumes of matter at high repetition rates will give the unique opportunity to investigate nuclear reactions and fundamental interactions process under extreme plasma conditions [1]. In this context, use of targets with nanostructured surfaces is giving promising indications to reproduce plasma conditions suitable for measurements of thermonuclear reactions rates, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Therefore, the interaction of nanosecond (ns) lasers with solid targets is well suited to generate extreme plasma environments at energy levels higher than the normal range. At the LENS laboratory in Catania, Italy, nanowire targets made of different materials are irradiated by using an infrared laser with an intensity of 10 12 W/cm 2 , a pulse duration of 6 ns, and an energy of 2 J [44,45]. It was found that, in the nanowire form, nanostructures on the surface of the target can absorb laser energy with very high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the interaction of nanosecond (ns) lasers with solid targets is well suited to generate extreme plasma environments at energy levels higher than the normal range. At the LENS laboratory in Catania, Italy, nanowire targets made of different materials are irradiated by using an infrared laser with an intensity of 10 12 W/cm 2 , a pulse duration of 6 ns, and an energy of 2 J [44,45]. It was found that, in the nanowire form, nanostructures on the surface of the target can absorb laser energy with very high efficiency.…”
Section: Introductionmentioning
confidence: 99%